FEDERALISM, INSECURITY, AND THE PERSISTENT AGITATIONS AMONG ETHNIC GROUPS IN NIGERIA’S FOURTH REPUBLIC: ANY WAY FORWARD? - TEMITOPE EMMANUEL ABIODUN; IBRAHIM ADEDAYO OYEWOLE; ENOCH AKINLOLUWA MAKINDE (International Studies Journal)
The paper examined rationales behind persistent agitations among ethnic groups in Nigerian federalism leading to various degrees of insecurity situations. Federalism have been largely accepted as the better form of government in a heterogeneous society such as Nigeria, however, the kind of federal system operating in Nigeria has created many problems because diverse ethnic and religious groups are unceremoniously brought together under one umbrella. The paper made used of qualitative approach and adopted group and frustration-aggression theories as its theoretical framework. Data were obtained through official publications, journals, textbooks, newspapers and reports. Findings revealed that the current pseudo-federal setup in Nigeria is indeed a major contributory factor to persistent ethnic agitations which have led to diverse insecurity cases in the fourth republic. Colonial policy and legacy further put Nigeria in a precarious position with ethnic groups suspecting one another, thus, making unity in diversity a herculean task. Also, the imperfections in the military bequeathed constitution which concentrated power on a particular tier of government and making resource control by the subordinating units difficult. The paper recommended among others a rejig of 1999 constitution to accommodate all ethnic groups and proper arrangement of political positions in the country. The need for dialoguing as a means of carrying ethnic groups (especially the minorities) along with a view of critically addressing issues that is germane to them. To ameliorate tensions that bring about agitations in Nigerian federalism, equality and justice in power and resource allocation among ethnic groups must be prioritised.